Uncovering Local Cultural Values Behind Income Accounting Practices By Ilabulo Sellers: Islamic Ethnomethodology Study - Thalib, Mohamad Anwar; Malik, Adelia; Ibrahim, Cindriyati; Ahaya, Maryam S. (IAIN Langsa, 2023)
This study aims to reveal the local cultural values behind income accounting practices by ilabulo sellers. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. The results of the study show that ilabulo sellers use their income to finance personal needs, such as making this income as capital to return to selling ilabulo, finance household needs, and in addition to their children's snacks. Furthermore, the ilabulo sellers use their income to share among themselves, such as with scavengers. The income accounting practice is driven by compassion (motoliango). In the culture of the Gorontalo people, there is lumadu (expression) “delo tombowata lo tabo wau labiya